Sie sind auf Seite 1von 1
Belastungsfall Biegelinie Durchbiegung Neigung w´ = tan 1 3 2 1 F x Fa Fa
Belastungsfall
Biegelinie
Durchbiegung
Neigung
w´ = tan
1
3
2
1
F
x
Fa
Fa
2
w(x) =
ax
3
w(a) =
w
(a) =
6
EI
a
3
EI
2
EI
2
M
2
Ma
2
Ma
w(x) =
x
w(a) =
w
(a) =
2
EI
2
EI
EI
3
4
2
3
4
4
3
qa
x
x
x
qa
qa
w(x) =
6
4
+
w(a) =
w
(a) =
2
3
4
24
EI
8
EI
6
EI
a
a
a
4
a
3
2
a
Fa
Fa
x
w
=
w
(a) =
2
2
48 EI
16
EI
3
3
Fa
x
4
x
w(x) =
16 EI
a
3
3
a
5
0
x
b
2
2
F
b
c
w(b)
a
w(b) =
w
(
0
) =
1
2
2
2
b
+ c
Fbc
x
a
x
3
EI
a
w(x) =
1
+
6
EI
a
c
bc
w(b)
a
w
(a) =
1
für b > c
gilt:
2
c
+ b
b
x
a
2
2
a
+
c
Fcb
a
x
a
+
b
(x
a)
*
x
=
b
w(x) =
3 b
6
EI
a
b
bc
*
a
+
c x
w
=
w(b)
max
3 c
a
6
2
3
für
M
= M
gilt:
a
M
a
x
x
1
2
(
1
w
( 0 ) =
2
M
+
M
)
w(x) =
+
2
1
2
6
EI
6
EI
a
3
a
M
a
1
w
=
max
a
8
EI
2
2
3
M
a
x
x
w
(a) =
(
2
M
+
M
)
2
1
2
+
2
3
x
+
6
EI
6
EI
a
2
3
a
a
7
2
3
4
3
4
5 qa
qa
x
x
a
qa
x
w
=
w
=
w
(a) =
w(x) =
1
24
EI a
2
+
max
a
a
2
384 EI
24
EI
8
0
x
a
2
F ab
Fab
b
w
(
w(a
+
b)
=
0
) =
1
2
3 EI
+ a
6
EI
Fab x
x
w(x) =
1
2
w
(a) =2 w (0)
6
EI
a
2
Fa
b
w
=
max
2
a
x
a + b
Fb
2 a
9
3
EI
w
(a
+
b)
=
1
+
2
2 EI
3 b
Fa (x
a)
2
b
+ 3 b(x
a)
a
w(x) =
x * =
2
6
EI
a
a
3
2
(x
a)
2
a